Age‐friendly initiative needs assessment survey: Los Angeles City and County employees: Other innovative programs and practices. (7th December 2020) - Aguilar, Iris; Lloyd, Donald A; Trejo, Laura; Aranda, Maria P
Abstract: Background: The City and County of Los Angeles Age‐Friendly Cities initiative, Purposeful Aging Los Angeles (PALA), 2017 needs assessment included an online survey of the workforce expected to implement age friendly policies and programs. The aim of this study was to describe the rate and characteristics of family caregivers within in the City and County workforce (employees). The overall response rate was 6.5% (City 4.5%, County 7.5%) for a final sample size 9, 330. The category of family caregiver was derived from the following survey questions: 1) Are you or someone else in your home caring for a family member or friends who are experiencing problems/thinking that is affecting their ability to work or live a normal life? and 2) Are you a family caregiver? The analysis revealed that 34% of all respondents were family caregivers with an almost even number of male to female ratio. Among all caregivers, the mean age for caregiving for someone with cognitive impairment not diagnosed dementia was 47 and diagnosed AD/Dementia was 49. The majority of caregivers (all types) were caring for either a child/children under the age of 18 (42.1%) followed by a parent(s) (23.1%). Nearly 15% of caregivers of adults with cognitive impairment reported caring for a child/children under the age of 18. When caregivers of adults with cognitive impairment were asked "what type of help might be most useful?", a higher preference for services was indicated by those aged 45‐64 who selected all the help types as most useful (information, symptom management, someone to talk to, ID lost person, diagnosis and help with care, legal, support group, caregiving financial support, chores/respite, day care, out‐of‐home placement). The current family caregiving research literature suggests that family caregivers experience higher rates of depression, anxiety, and social isolation due to the caregiving demands. Caregiving demands have the potential to create work‐family conflicts that are important for employers to consider when designing wellness programs, and other supportive employment programs. It is critical to identify ways to address caregiving implications on social services, healthcare, and the environment.